Neusis - Arabatzis, Theodore; Stathis Arapostathis; Iraklis Katsaloulis; Aristotle Tympas (The perils of prediction in the Physical Sciences: Historical and epistemological perspectives (in Greek), 2025)
This special issue of the journal Neusis focuses on the role of prediction in scientific practice and examines the following questions: How has the role and status of prediction changed historically? How is the gap between theory and prediction of specific phenomena bridged? What is considered a valid and successful prediction in different areas of the natural sciences?